Dermatitis herpetiformis misdiagnosed and treated as tinea cutis glabrae - Stawczyk-Macieja, Marta; Szczerkowska-Dobosz, Aneta; Jaśkiewicz-Nyckowska, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . Dermatitis herpetiformis is a rare bullous disorder. Autoimmunological disturbances associated with hypersensitivity to gluten play the main role in the etiopathogenesis of the disease. Clinical manifestations include polymorphic skin lesions which may cause diagnostic difficulties. Objective. To present a case of dermatitis herpetiformis diagnosed and treated without any clinical improvement as tinea cutis glabrae. Case report . A 20-year-old male patient was admitted for the evaluation of polymorphic skin lesions of 7-month duration distributed symmetrically on the skin of elbows, knees, face and the gluteal and sacral region. The patient was previously treated with systemic and topical antimycotic drugs. Due to a typical distribution of skin lesions as well as symptoms reported by the patient, we started to suspect Duhring’s disease. The diagnosis was confirmed by direct immunofluorescence of skin biopsy and serological tests. Systemic treatment with dapsone and a gluten-free diet led to clinical improvement. Conclusions . The morphology and localization of skin lesions in Duhring’s disease may be similar to the clinical presentation of fungal infection of the skin, which in equivocal cases should be excluded by a mycological test.